(untitled) (Fiep Bulletin - online, 2012)
LEARNINGPE teaching is compulsory at primary (3-11 year olds) and secondary schools (11-19 year olds) in Italy.Secondary school PE teachers are specialists and have degrees in physical education together with the SIS (SchoolInterateneo for Secondary School teacher specialisation) teaching diploma of specialisation.During the SIS training preservice teachers have 300 hours of tutoring by inservice teachers in PE classes.Two teachers working together (pre/inservice) helps transmit new knowledge from preservice to inservice and so itpermits transmit from university studies on PE science to best practice in bi-univocal way.Inservice teachers give preservice teachers knowledge concerning didactics.The survey aims at defining this information/training exchange among inservice/preservice teachers.The method is based on questionnaires, given to inservice PE teachers taking part in SIS Training Program (STP).The questionnaires were made up of closed answers and multiple choice, concerning: inservice/preservice PE teachersrelationship; preservice teachers participation in inservice activities; value of inservice training through a training programby PE inservice teachers; satisfaction rate of inservice PE teachers within SIS tutoring program activities;comparison between PE and Italian-Maths teachers training and the PE considered equal to academic subjects.A comparison between PE and Italian maths teachers training considered PE equal to the academic subject.The questionnaires were given to 116 inservice teachers from secondary schools (11-19 year olds) taking part inSTP.Each inservice teacher coached a preservice teacher for 500 hours, aggregate amount 50,000 hours of STP.The survey lasted two years (2004 – 2006) at the SIS-University of Turin (Italy)The final data was 4000.The data indicates the positive trend of perception in the relationship between initial university training andcontinuous inservice training through cooperation between university andsecondary schools taking part in STP.The comparison (Italian maths/PE) highlighted the uniformity among the different subjects giving them equaldignity and educational value thanks to shared training in indirect topics and shared aspects within the training program.